Prevalence, histopathology and treatment of ear mites (Otodectes cynotis Hering) infestation in cats in Selangor, Malaysia - Phan, Kim Thai (2011)
Otodectes cynotis is the most common infesting ear mite documented in 85% of cases of otitis externa in cats. Though O. cynotis is an important common cause of otitis externa, there is a lack of information on its prevalence in the feline population and the factors that could affect its potential survival in the ear canal of this species. Thus, the first objective in this study was to estimate the prevalence of Otodectes cynotis in cats at the University Veterinary Hospital, Universiti Putra Malaysia, submitted for treatment between March 2010 and May 2010. A total of 324 cats, age ranging between 2 and 96 months were examined. Samples were taken from both ears using cotton-tipped swabs. Thirty point six percent (30.6%) of cats were positive for O. cynotis. However, there was no statistical difference between sex, breed, style of living and type of hair coat. This study found that there was a significant difference (P<0.05) between 2 age groups: 3 years old and younger, and 3 years old and older. Clinical signs associated with ear mite infestation such as head shaking,ear scratching, ear discharges, alopecia and crusts at the pinna are significantly correlated with the presence and absence of mites. Tissues from the infected external ear canals were sampled and fixed in 10% buffered formalin. The tissues were embedded in paraffin wax, later sectioned for about 4 μm thickness and stained with Hematoxylin and Eosin stains. The results showed that the epidermis was generally moderate but sometimes severely hyperplastic, exhibited as orthokeratotic and/or parakeratotic hyperkeratosis and acanthotic thickening of epithelium. In addition, slight to moderate perivascular infiltration of inflammatory cells consisting of lymphocytes, plasma cells and some macrophages were also seen in the dermis. Ceruminous glands were dilated and full of secretion in the lumen associated with the proliferation of hair follicle and sebaceous gland cells and folliculosebaceous hamartoma. Different groups of cats and kittens with ear mite infestation were treated with ivermectin at 200μg/kg, 300μg/kg and 400μg/kg dosage. Each cat was given 3 treatments on day 0, 7, 14 of each dosage level. All cats were examined for ear mites on day 0, 7, 14, 21, 28and 35. It was found that the efficacy of ivermectin was 100% by day 14 in all treatment groups. However, there was no significant difference between each treatment group.